2017
DOI: 10.1038/s41467-017-01031-3
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional scanless holographic optogenetics with temporal focusing (3D-SHOT)

Abstract: Optical methods capable of manipulating neural activity with cellular resolution and millisecond precision in three dimensions will accelerate the pace of neuroscience research. Existing approaches for targeting individual neurons, however, fall short of these requirements. Here we present a new multiphoton photo-excitation method, termed three-dimensional scanless holographic optogenetics with temporal focusing (3D-SHOT), which allows precise, simultaneous photo-activation of arbitrary sets of neurons anywher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
207
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(213 citation statements)
references
References 54 publications
4
207
2
Order By: Relevance
“…Rather, these data demonstrate that simple depolarization of excitatory neurons in each cortical layer inherently engages gamma band activity, plausibly according to the commonly employed PING model (Pyramidal-Inhibitory neuron-Network-Gamma) (Tiesinga & Sejnowski, 2009;Buzsaki & Wang, 2012). Future work with much more sophisticated optogenetic methods, such as multiphoton holography (Papagiakoumou et al 2010;Packer et al 2015;Carrillo-Reid et al 2016;Pegard et al 2017), might be able to better recreate even more physiological patterns of activity to ask how different ensembles of neurons with functionally identified properties (such as common orientation tuning) differentially contribute to gamma activity.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Rather, these data demonstrate that simple depolarization of excitatory neurons in each cortical layer inherently engages gamma band activity, plausibly according to the commonly employed PING model (Pyramidal-Inhibitory neuron-Network-Gamma) (Tiesinga & Sejnowski, 2009;Buzsaki & Wang, 2012). Future work with much more sophisticated optogenetic methods, such as multiphoton holography (Papagiakoumou et al 2010;Packer et al 2015;Carrillo-Reid et al 2016;Pegard et al 2017), might be able to better recreate even more physiological patterns of activity to ask how different ensembles of neurons with functionally identified properties (such as common orientation tuning) differentially contribute to gamma activity.…”
Section: Discussionmentioning
confidence: 73%
“…; Pegard et al . ), might be able to better recreate even more physiological patterns of activity to ask how different ensembles of neurons with functionally identified properties (such as common orientation tuning) differentially contribute to gamma activity.…”
Section: Discussionmentioning
confidence: 99%
“…Two‐photon (2P) optogenetic stimulation provides spatially precise cellular level stimulation by minimizing out‐of‐focus neuron excitation, often in combination with complementary techniques like temporal focusing and soma‐restricted opsin expression . To stimulate multiple neurons, distributed holographic light patterns can be generated and dynamically controlled using spatial light modulators (SLMs) . These patterns are frequently composed of cell soma sized “spots,” which are focused up to a few hundred micrometers deep into the brain to stimulate specific pre‐chosen neurons with high temporal precision …”
Section: Introductionmentioning
confidence: 99%
“…This was done either by generating multiple diffraction-limited spots that were scanned simultaneously across multiple cell somata [18][19][20] , or by using computer generate holography (CGH) to produce light patterns covering multiple cell somata at once 21 , thus optimizing the temporal precision of the photostimulation 22 . Recently, several research groups [23][24][25][26][27] have shown that using a two-step wave front shaping combined with temporal focusing (TF) [28][29][30][31] it is possible to generate multiple high resolution extended light patterns in 3D, a technique we named multiplexed temporally focused light shaping (MTF-LS). These approaches led to the first demonstrations of neural circuit manipulation in 3D 25,26 , yet the need of using conventional high numerical aperture (NA) objectives limited their use to circuits in superficial (≤ 300 µm) cortical areas or to in-vitro applications.…”
Section: Introductionmentioning
confidence: 99%